Hand hygiene strategies - Yazaji, Eskandar Alex (Co-Action Publishing, 2011)
Hand hygiene is one of the major players in preventing healthcare associated infections. However, healthcare workers compliance with hand hygiene continues to be a challenge. This article will address strategies to help improving hand hygiene compliance.